English for engineering: (aerospace engineering, mechanical engineering, energy and utilities, manufacturing, materials) - VÂLCEA, Cristina-Silvia (Presa Universitară Clujeană, 2022)
This book is addressed to English intermediate professionals who may need to improve their English knowledge and it offers a satisfying Journey along five significant domains in engineering that will strengthen their control of technical vocabulary in a wide variety of exercises. The book encourages vocabulary extension by exercises that deal with synonyms, fill-in exercises which aim at bracing the comprehension of the logic of the text, matching exercises that stimulate particular understanding of concepts, multiple choice exercises that prompt professionals to associate words in verbal phrases, in idioms, etc. Every exercise has at least a twofold purpose: that of instructing the professional with the information that the text provides and that of offering language and vocabulary practice in order to stabilise and improve their English knowledge. There is a key at the end of the book which provides solutions for most of the exercises.